2005
DOI: 10.1002/ijc.20997
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma MMP9 in integrin α1‐null mice enhances lung metastasis of colon carcinoma cells

Abstract: Inhibitors of matrix metalloproteinases (MMPs) were developed as anticancer agents based on the observation that MMPs facilitate local tumor spread and metastasis by promoting matrix degradation and cell migration. Unfortunately, these inhibitors were unsuccessful in the clinical treatment of several cancers, including lung cancer. A possible reason contributing to their failure is that MMP activity is critical for the generation of inhibitors of tumor angiogenesis, including angiostatin. Thus, MMPs might play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 20 publications
5
49
0
1
Order By: Relevance
“…Thus, high expression of MMP-2 and MMP-9 may be used to characterize the behaviors of colorectal carcinoma (38,39). Moreover, high colorectal MMP-9 expression has been implicated in lung metastases (40) and tumor cell resistance to proapoptotic and p53 effects, as well as poor efficacy in postoperative adjuvant chemotherapy (41). In vitro, MIF also was shown to promote cell invasiveness through macrophage secretion of MMP (42).…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…Thus, high expression of MMP-2 and MMP-9 may be used to characterize the behaviors of colorectal carcinoma (38,39). Moreover, high colorectal MMP-9 expression has been implicated in lung metastases (40) and tumor cell resistance to proapoptotic and p53 effects, as well as poor efficacy in postoperative adjuvant chemotherapy (41). In vitro, MIF also was shown to promote cell invasiveness through macrophage secretion of MMP (42).…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…MMPs have been correlated with cancer prognosis clinically and histopathologically (Leeman et al, 2003). One, in particular, MMP-9 (a 92-kDa type IV collagenase or gelatinase B) has a role in tumor invasion, angiogenesis and metastasis (Bernhard et al, 1994), and its level is related to angiostatin synthesis and systemic metastasis in animal models (Basile et al, 2004;Chen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Chen, et al, showed that treatment of CT26 (colon carcinoma cells) inoculated mice with 40 mg/kg/day of doxycyclin starting immediately or 2-weeks after tumor cell injections resulted in fewer but larger and more vascularized lung tumors. On the other hand, when therapy started at the time of tumor injections, mice had fewer lung tumors than mice treated 2-weeks after injection of colon carcinoma cells [83]. This suggests that the time and/or the frequency of the treatment have significant effect on development of lung experimental metastasis.…”
Section: Survival Curve Of Mice Injected With 1x10mentioning
confidence: 99%
“…The increased vascularization was attributed to decreased production of angiostatin by MMP-9 [83]. Thus, MMP-9 inhibitors may have a null or pro-tumorigenic effect when administered intravenously.…”
Section: Survival Curve Of Mice Injected With 1x10mentioning
confidence: 99%
See 1 more Smart Citation